Implementasi Iptek untuk Standardisasi, Pemasaran, dan Distribusi Produk Kerajinan Sulaman Kain Karawo bagi Usaha Mikro, Kecil, dan Menengah (UMKM) di Kabupaten Gorontalo - Ismet Sulila; Tineke Wolok; Abdul Rahman Pakaya (Universitas Mathla'ul Anwar Banten, 2019)
THE IMPLEMENTATION OF IPTEK (SCIENCE AND TECHNOLOGY) OF PRODUCT STANDARDIZATION, MARKETING, AND DISTRIBUTION OF KARAWO FABRIC EMBROIDERY CRAFTS AT GROUP OF MICRO, SMALL, AND MEDIUM ENTERPRISES OF GORONTALO DISTRICT. Community service through a development program of Karawo embroidery as the regional competitive product was conducted in Religious Tourism Village of Bongo in Gorontalo District. The program was focused on a gradual and measurable concrete effort in improving Community Economic Empowerment. Specific targets that should be achieved through the program were product standardization, marketing, and distribution. In implementing the program, it is necessary to have a method which is able to achieve the targeted results. Thus, the applied approach method was unique and different which encompassed: 1) determination of the solved problem priority scale, 2) doing reconstruction and improvement gradually, 3) improvement based on local community character approach, 4) implementation of science and technology. Based on the study of the implementation of science and technology, the result showed that: 1) the implementation of science and technology of Karawo product standardization could give a limit of product quality based on market need, price, and product users. 2) The implementation of science and technology of marketing through the use of social media could improve market demand for the varied product of Karawo in local and national level. 3) The implementation of science and technology of distribution of varied product to consumers performed through online media and transportation could distribute varied product to the consumers. Overall, it was concluded that the implementation of science and technology by university/ college had given real contribution to the effort of improvement of empowerment and welfare of the community.